Species Composition and Mangrove Forest Structure in Pulau Sebuku, South Kalimantan KOMPOSISI JENIS DAN STRUKTUR HUTAN MANGROVE DI PULAU SEBUKU, KALIMANTAN SELATAN - R Rodlyan Ghufrona; Cecep Kusmana; Omo Rusdiana (Jurnal Silvikultur Tropika, 2015)
Pulau Sebuku mangrove forest, South Kalimantan, is part of Pulau Sebuku Nature Reserve that needs to be protected as close as naturally. This study is aimed to explore the species composition and structure of mangrove forest in Pulau Sebuku. The results showed that Pulau Sebuku mangrove forest has low species diversity and high evenness. Total species of mangrove tree, forest regeneration, and other habitus consists of 10 species (Bruguiera gymnorrhiza, B. parviflora, Ceriops tagal, Rhizophora apiculata, R. mucronata, Sonneratia alba, Heritiera littoralis, Xylocarpus granatum, Nypa fruticans, and Acrostichum aureum). R. mucronata (bakau) is the dominant species in almost all locations of observation. Horizontal structure of Pulau Sebuku mangrove forests tend to L-form, which evolved towards a balanced uneven-age forest. Based on the floristic composition, structure and general appearance of the forest, mangrove forest communities in Pulau Sebuku grouped into 3 types, among others: shrub communities (bakau-perepat), young mangrove communities (bakau and bakau-lenggadai), and nypa community.Key words : forest structure, mangrove forest, pulau sebuku, species composition.